French Colonial Trade Patterns and European Settlements. Issue 3 (September 2018) - El Kallab, Tania; Terra, Cristina
Abstract We construct a new database relying on various primary historical sources containing information on the value of French sectoral trade between 1880 and 1913 in order to assess the contemporaneous effects of colonial European settlements on French trade patterns. Our empirical results show that French colonies with more European settlements traded more with France. The impact is stronger with respect to the imports of raw materials and exports of manufactured goods from France to their colonies, suggesting that those territories were a source of resources for France and a market for its products. European settlements in colonies other than the French ones did not impact the trade of those colonies with France. We also explore to what extent the impact of European settlements on trade was exerted through the channel of the institutions brought by the settlers. Separating the part of European settlements associated with institutions, we find that the settlements associated with stronger institutions in French colonies had a positive impact on trade with those colonies. No significant impact was found for non-French colonies.